The Influence Of Work Environment And Motivation On Employee Spirit At Pt Perkebunan Nusantara IV, Gunung Meliau Palm Oil Mill Work Unit - Dila Sandi; Devi Yasmin (UNIVED Press, 2024)
This study aims to identify and analyze the influence of the Work Environment and Motivation on the Work Spirit of employees at PT Perkebunan Nusantara IV, Gunung Meliau Palm Oil Mill Work Unit. The population in this study consists of 125 individuals, using a saturated sampling technique. Data collection techniques in this study include interviews and questionnaires. The analytical tools used in this research are instrument tests, classical assumption tests, multiple linear regression analysis, correlation coefficients, determination coefficients, F-tests, and T-tests. The results of the study show that the work environment and motivation affect work spirit both simultaneously and partially. Therefore, to enhance work spirit, both the work environment and motivation must be well managed